DESIGN OF THE PROPOSED IMPROVEMENT TO OVO’S ELECTRONIC MONEY PAYMENT SERVICES IN GRAB ONLINE TRANSPORTATION SERVICES - Swaraswati, Dinnur; Pujiyanto, Eko; Hisjam, Muhammad (Jurnal Ilmiah Teknik Industri, 2020)
The advancement of science and technology in the world has brought many influences to the changes in people's behavior and habits, one of that is the technology payment system adopted as an electronic payment system. As an electronic payment instrument, OVO cooperates with one of the online-based transportation services, Grab. However, the success of a company can be seen from the quality of service in meeting the satisfaction of the community or customers. The success of the company in providing quality services can be determined by the Service Quality (Servqual) approach, that is a method used to measure service quality from the attributes of each dimension, so that a gap value will be obtained that is the difference between consumers' perceptions of services that has been received in the hope that will be received. The objective to be achieved is to propose a design in the form of alternative solutions for the priority of improving the quality of electronic money OVO services in Grab applications. Data were collected through a questionnaire using non-probability sampling techniques with a total sample of 140 respondents. The study found the main problems, namely in the dimensions of compensation, responsiveness, and Privacy/Security.